Optimizing HyFlex Learning: Pedagogical, Technological, and Policy Perspectives - Hidayati, Nur; Sindangsari, Laura Putri; Mustika, Nisa (Sinergi International Journal of Education, 2025)
This narrative review explores the implementation, readiness, and impact of HyFlex (Hybrid-Flexible) learning models in higher education, a format increasingly adopted to support student-centered and technologically enriched learning. The objective is to synthesize empirical and conceptual literature to assess the model’s effectiveness and identify persistent challenges. Data was collected from Scopus, ERIC, Web of Science, and Google Scholar, using key phrases such as "HyFlex learning," "implementation challenges," and "student engagement in hybrid-flexible classrooms." Inclusion criteria focused on peer-reviewed studies published within the last five years. The review finds that successful HyFlex implementation depends on robust digital infrastructure, faculty adaptability, and targeted instructional strategies that support both in-person and online learners. Studies demonstrate increased student satisfaction, participation, and academic performance when these conditions are met. However, systemic issues such as unequal access to digital tools, limited institutional support, and insufficient policy frameworks remain significant barriers. Literature consistently suggests that faculty training, real-time feedback integration, and supportive policies are essential to optimizing the model’s impact. The study concludes that while HyFlex is a promising innovation, its success requires coordinated structural, technological, and pedagogical interventions. This paper advocates for stronger institutional and governmental policies, cross-unit collaboration, and ongoing research into student experience and faculty development to enhance the efficacy and equity of HyFlex learning environments.